2010
DOI: 10.1111/j.1540-4781.2010.01054.x
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Language Learning Attitudes and Motivation: Lessons From an Interview Study of Dyslexic Language Learners

Abstract: The aim of our study was to provide an insider's account of the dynamics of language learning motivation in Hungarian students with dyslexia. For this purpose, we conducted qualitative interviews with 15 students who studied foreign languages in a variety of educational settings. In this article, we drew up a dynamic model of language learning motivation based on our interview data with dyslexic learners. We argued that goals, attitudes, and motivated behavior form a closely interrelated coadaptive system, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 35 publications
1
37
0
1
Order By: Relevance
“…Some researchers have explored alternative methods in conducting motivation research, such as qualitative interviews (Csizér, Kormos, & Sarkadi, 2010;Ushioda, 2001) or a mixed-methods approach (Busse & Walter, 2013;Cai & Zhu, 2012). This study aims to explore and relate learners' feedback about tasks to learner motivation, primarily from a qualitative perspective.…”
Section: Motivation In Foreign Language Educationmentioning
confidence: 98%
“…Some researchers have explored alternative methods in conducting motivation research, such as qualitative interviews (Csizér, Kormos, & Sarkadi, 2010;Ushioda, 2001) or a mixed-methods approach (Busse & Walter, 2013;Cai & Zhu, 2012). This study aims to explore and relate learners' feedback about tasks to learner motivation, primarily from a qualitative perspective.…”
Section: Motivation In Foreign Language Educationmentioning
confidence: 98%
“…According to Dörnyei (2001), 'the downside of quantitative methods is that they average out responses across the whole sample or subsample, and by working with concepts of averages it is impossible to do justice to the subjective variety of an individual life ' (p. 193). Csizér et al (2010) pointed out that it is very important to carry out qualitative studies in order to explore the dynamic and fluctuating nature of language learning motivation. In accordance with his conceptualization of L2 motivation from a self perspective, Dörnyei (2005) suggested that motivational change may involve the elaboration of the ideal L2 self and the internalization of the ought-to L2 self.…”
Section: L2 Motivational Changementioning
confidence: 99%
“…The motivation of L2 learners is affected by a number of contextual variables such as learners' immediate learning environment and social and linguistic milieu (e.g., Clément & Kruidenier, 1983;Csizér, Kormos, & Sarkadi, 2010;Dörnyei & Csizér, 2002;Gardner, 1985). These factors (i.e., learners' immediate learning environment and social and linguistic milieu) may cause fluctuation in the intensity of L2 motivation during the L2 learning process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown, motivation is such an important factor that leads to successful learning outcomes. If motivation could be generated and gradually increased, learning outcomes would be expected to improve over time (Csizer, Kormos, & Sarkadi, 2010;Hsiao, Tu, & Chung, 2012).…”
Section: B Research Questionsmentioning
confidence: 99%